Antibacterial Activity Analysis of Hydroxyapatite Based Materials with Fluorine and Silver - González Torres, Verónica; Hernández Guevara, Esteban; Castillo Martínez, Nydia Alejandra; Rosales Aguilar, Martha; Díaz Trujillo, César Gerardo (Revista Mexicana de Ingenieria Biomedica, 2021)
This investigation aims to evaluate the antibacterial activity of nanostructured hydroxyapatite based materials doped with silver and fluorine, to be used as a biomaterial with antibacterial activity. Four different formulations were prepared by combustion method: hydroxyapatite, hydroxyapatite-fluorine, hydroxyapatite-silver-fluorine and hydroxyapatite-silver, with 2% of the doping agents. X-ray diffraction technique was used to determine the mineralogy, identifying the presence of Ca5(PO4)3OH, Ca2P2O7, Ag3PO4, AgCa10(PO4)7 Ca5(PO4)3F and CaF2 phases for the studied samples. Scanning electron microscopy was used to study the morphological structure and it showed homogeneous crystallization of the hydroxyapatite and the inclusion of dopant agents. The antibacterial activity was determined using a modified inhibition test zone to observe if the bacteria (E. faecalis) was susceptible to the antimicrobial agent by the appearance of the zone of inhibition on the agar plate. Both the hydroxyapatite-silver and the hydroxyapatite-silver-fluorine materials generated an inhibition zone. It was possible to determine the minimum inhibitory concentration needed to kill most viable organisms after 48 hours of incubation using the broth microdilution method, resulting in 75 µg/ml and 200 µg/ml for the hydroxyapatite-silver and the hydroxyapatite-silver-fluorine formulation, respectively. These materials could be used for the development of new biomaterials that can be used in dental applications.